MS treatment de-escalation: review and commentary - Selmaj, Krzysztof; Hartung, Hans-Peter; Mycko, Marcin P; Selmaj, Igor; Cross, Anne H (Journal of neurology, 2024)
Almost all currently licensed disease-modifying therapies (DMTs) for MS treatment require prolonged if not lifelong administration. Yet, as people age, the immune system has increasingly reduced responsiveness, known as immunosenescence. Many MS DMTs reduce the responsiveness of the immune system, increasing the risks for infections and possibly cancers. As people with MS (pwMS) age, it is recognized that inflammatory MS activity declines. Several studies have addressed de-escalation of DMTs for relapsing MS under special circumstances. Here, we review evidence for de-escalating DMTs as a strategy that is particularly relevant to pwMS of older age. Treatment de-escalation can involve various strategies, such as extended or reduced dosing, switching from high-efficacy DMTs having higher risks to moderately effective DMTs with lesser risks, or treatment discontinuation. Studies have suggested that for natalizumab extended dosing maintained clinical efficacy while reducing the risk of PML. Extended interval dosing of ocrelizumab mitigated the decline of Ig levels. Retrospective and observational discontinuation studies demonstrate that age is an essential modifier of drug efficacy. Discontinuation of MS treatment in older patients has been associated with a stable disease course, while younger patients who discontinued treatment were more likely to experience new clinical activity. A recently completed 2-year randomized-controlled discontinuation study in 260 stable pwMS > 55 years found stable clinical multiple sclerosis with only a small increased risk of new MRI activity upon discontinuation. DMT de-escalation or discontinuation in MS patients older than 55 years may be non-inferior to continued treatment with immunosuppressive agents having higher health risks. However, despite several small studies, a definite conclusion about treatment de-escalation in older pwMS will require larger and longer studies. Ideally, comparison of de-escalation versus continuation versus discontinuation of DMTs should be done by prospective randomized-controlled trials enrolling sufficient numbers of subjects to allow comparisons for MS patients of both sexes within age groups, such as 55-59, 60-65, 66-69, etc. Optimally, such studies should be 3 years or longer and should incorporate testing for specific markers of immunosenescence (such as T-cell receptor excision circles) to account for differential aging of individuals.
Keywords: Multiple Sclerosis; De-escalation; Disease-modifying therapies; Immunosenescence; Immunologic Factors; Humans; imunologické faktory; roztroušená skleróza; lidé; Multiple sclerosis